THE SELFABSORPTION SAN LUIS POTOSIECTRUM OF THE TRIPLET SYSTEM OF HE I - BLOCK, RA (UNAM, Observatorio Astronómico Nacional, CD MEXICO, DF, MEX, 1968)
The relative line intensities for the triplet system in He I, have been re-computed for various nebular optical depths at ?3888. The profile of the line has been considered due to its importance. The electron collisions have not been taken into account si
BOL OBS TONAN TACUB
Keywords: SELF, ABSORPTION SPECTRUM, TRIPLET SYSTEM; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS